Hidrólise de nucleotídeos de adenina em plaquetas de pacientes com diferentes níveis de colesterol e sua relação com o processo inflamatório - Duarte, Marta Maria Medeiros Frescura (2006)
The activity of NTPDase (EC 3.6.1.5, apyrase, CD39) was verified in platelets from patients with increasing cholesterol levels. A possible association between cholesterol levels and inflammatory markers, such as oxidized low density lipoprotein (oxLDL), highly sensitive C-reactive protein (hsCRP) and oxLDL autoantibodies was also investigated. The following groups were studied: group I (< 150 mg/dl), group II (151 to 200 mg/dl); group III: (201 to 250 mg/dl); group IV (> 251 mg/dl) of cholesterol. The results demonstrated that both ATP and ADP hydrolysis were enhanced as a function of cholesterol levels. The LDL levels increased concomitantly with total cholesterol levels. The triglyceride levels were increased in the group with total cholesterol above 251 mg/dl. oxLDL levels were elevated in groups II, III and IV. hsCRP was elevated in the group with cholesterol higher than 251 mg/dl. oxLDL autoantibodies were elevated in groups III and IV. TBARS content was enhanced as a function of cholesterol levels. In summary, hypercholesterolemia is associated with an enhanced of inflammatory response and ATP and ADP hydrolysis. The increase in NTPDase activity is possibly related to a compensatory response to the inflammatory and pro-oxidative state associated with hypercholesterolemia.